PCSK9 inhibitors reduces arterial stiffness in patients with acute coronary syndrome - Wang Liang; Wang Ruijie; Jiao Tiantian; Xu Linghao; Ji Endong; Jiang Yuanzhen; Wang Yuanqi; Liu Yehong; Li Jiming (Journal of Medical Biochemistry)
Background: This study focuses on uncovering the effects of proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors in attenuating arterial stiffness in patients with acute coronary syndrome (ACS) and atherosclerosis. Methods: A total of 71 ACS patients were enrolled in this study from April 1, 2022, to June 31, 2022. Patients were randomly assigned to two groups: one group received statin therapy combined with PCSK9 inhibitors (Evolocumab 140 mg or Alirocumab 75 mg every two weeks) (n = 36), and the other group received statins alone (n = 35). All patients underwent measurements of lipid metabolism and arterial stiffness at baseline, 1 month, and 6 months after treatment initiation. Statistical power analysis indicated that the sample size of 71 patients provided sufficient power to detect significant differences. Results: After 1 month, the group treated with statins and PCSK9 inhibitors showed significantly greater reductions in total cholesterol (TC), triglycerides (TG), low-density lipoprotein (LDL), and lipoprotein(a) [Lp(a)] levels compared to the statin-only group (p = 0.027 and p = 0.021, respectively). By the 6-month follow-up, significant reductions were observed in pulse wave velocity (PWV) and ankle-brachial index (ABI) in the combination treatment group (p < 0.05). However, no significant differences were observed between Evolocumab and Alirocumab in terms of arterial stiffness improvement (p > 0.05). Statistical power was sufficient to detect these changes. Conclusions: The findings suggest that PCSK9 inhibitors, when combined with statins, not only improve lipid metabolism but also reduce arterial stiffness, offering potential benefits for vascular health in patients with ACS and atherosclerosis. Further studies with larger sample sizes and longer follow-up periods are necessary to confirm these results.